Energetic electron lensing caused by Ganymede's magnetic field. (December 2022) - Herceg, M.; Jørgensen, J.L.; Merayo, J.M.G.; Denver, T.; Jørgensen, P.S.; Benn, M.; Kotsiaros, S.; Connerney, J.E.P.; Bolton, S.J.
Abstract: The micro Advanced Stellar Compass (μASC) continuously monitors high energy particle fluxes in Jupiter's magnetosphere while providing attitude reference for the Juno Magnetic Field investigation. The μASC camera head unit (CHU) serves as a energetic particle sensor monitoring the radiation environment at Jupiter by sensing electrons greater than 15 ​MeV that pass through the CHU shielding. A comparison of the energetic electron population sampled during many orbits reveals events observed when Juno is traversing Ganymede's M-shell. We present observations of energetic electron depletions related to the interaction with Ganymede's magnetic field. The magnitude and extent of these depletions is associated with Juno's proximity to the magnetic field line passing through Ganymede. Analysis of the observations reveal that the charged particle depletion likely arises from electron scattering in Ganymede's magnetic field, observed within ∼13° phase angle from the moon, beyond which the flux tubes refill due to diffusion. Highlights: The μASC >15 MeV electron observations reveals Ganymede's influence on the local energetic particle population. Ganymede causes a decrease (up to 52%) in energy electron flux that is central to and symmetrical about Ganymede's position. The Ganymede interaction region has a width of ∼26, 000 ​km, or ∼10 Ganymede radii.